Resonant plasmonic nanoslits enable in vitro observation of single-monolayer collagen-peptide dynamics - Semenyshyn, Rostyslav; Hentschel, Mario; Huck, Christian; Vogt, Jochen; Weiher, Felix; Giessen, Harald; Neubrech, Frank (ACS sensors, 2019)
Proteins perform a variety of essential functions in living cells and thus are of critical interest for drug delivery as well as disease biomarkers. The different functions are derived from a hugely diverse set of structures, fueling interest in their conformational states. Surface-enhanced infrared absorption spectroscopy has been utilized to detect and discriminate protein monomers. As an important step forward, we are investigating collagen peptides consisting of a triple helix. While they constitute the main structural building blocks in many complex proteins, they are also a perfect model system for the complex proteins relevant in biological systems. Their complex spectroscopic information as well as the overall small size present a significant challenge for their detection and discrimination. Using resonant plasmonic nanoslits, which are known to show larger specificity compared to nanoantennas, we overcome this challenge. We perform in vitro surface-enhanced absorption spectroscopy studies and track the conformational changes of these collagen peptides under two different external stimuli, which are temperature and chemical surroundings. Modeling the coupling between the amide I vibrational modes and the plasmonic resonance, we can extract the conformational state of the collages and thus monitor the folding and unfolding dynamics of even a single monolayer. This leads to new prospects in studies of single layers of proteins and their folding behavior in minute amounts in a living environment.